Free movement of data in the European Union: opportunity or big challenge in a use of artificial intelligence? - Breskienė, Ineta (Vilnius University Open Series, 2020)
This article analyses the current situation in the European Union related to the free movement of data, relationship between personal data, non – personal data and their use in artificial intelligence technology. Despite the European Union’s efforts to facilitate the free movement of data, some relevant obstacles are currently being observed. Artificial intelligence technology faces difficulties in using data. Despite the fact that large amounts of data are now increasingly accessible to such technology, its ability to de-anonymize data poses risks of turning simple data into personal data and making its use a challenge for artificial intelligence developers. The issues raised are sensitive and some regulatory changes should be made in the near future in order for the European Union to remain a leader in emerging technologies.